The development of the control of electronic cigarette use among youth in a community with village health volunteer participation in Chachoengsao province - Ruamsook, Tanawat; Auemeneekul, Naruemon; Kerdmuang, Suwattana; Rojpaisarnkit, Kunwadee; Chantian, Pimpat; Suramit, Bang-On (Thai Journal of Nursing, 2024)
This action research aimed to develop the control of E-cigarettes use among youth in a community with village health volunteer participation in Chachoengsao province. One hundred and sixty-eight participants were selected by purposive sampling technique. Questionnaires, semi-structured interview, focus group discussion and knowledge exchange forum were used in data collection including the activities in the phases of preparation, action, and evaluation. Descriptive statistics, t-test, and content analysis were used in data analysis. The results reveal that after the activity implementation, village health volunteers have significantly increased in awareness of E-cigarettes, laws and tobacco control, and negative attitude toward E-cigarettes (p < .05). Health personnel and community leaders also gained more confidence in controlling E-cigarettes use among youth through human potential development and creating supportive environment for tobacco control in community.